An Opportunity to Harmonise the Approach to Patients' Care Pathways for Rare and Complex Diseases: RarERN Path™ - Talarico, Rosaria; Marinello, Diana; Cannizzo, Sara; Palla, Ilaria; Ticciati, Simone; Gaglioti, Andrea; Rys, Andrzej; Milli, Carlo; Taruscio, Domenica; Mosca, Marta; Turchetti, Giuseppe (Frontiers in Health Services, 2022)
Organization always matters when discussing about healthcare, since it is fundamental in order to ensure the delivery of the most appropriate care to patients in the most appropriate way. Unfortunately, the Sars Cov-2 pandemic imposed a huge reorganisation of the healthcare systems, with several repercussions on the care of several chronic conditions, that was in many cases discontinued. This was the case of rare diseases (RDs), conditions that even under normal circumstances can experience diagnostic delays and difficulties in receiving appropriate care. The context of the European Reference Networks (ERNs) represents one of the most appropriate setting for the creation of organisational reference models for patients care pathways (PCP); as a matter of fact, the main mission of ERNs is to improve the care of RDs patients in Europe, through a patient-centered approach and thanks to a real multistakeholder involvement. For this reason, in the last years an extensive effort has been made towards the creation of a methodological approach aimed at providing organisational reference models for PCP in RDs across the diferent Member States. In fact, in order to develop the reference model, a structured methodology was created to enable the design of the PCP based on a deep sharing of expertise on high-quality care and characterized by a strong patient-centred approach: RarERN Path. Among the different stakeholders that need to be involved in planning strategic actions to ensure care also during an emergency, patients’ representatives, healthcare professionals, hospital managers and experts in healthcare organisation play a crucial role